Property rights, transaction costs, and the limits of the market - Carmine Guerriero (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2017)
Although the relevance of property rights and transaction costs for trade and innovation are well-known, we still lack a formal framework to think about their origins and interplay. Within trade interactions, fully protecting the original owners' property implies that some high-valuation potential buyers inefficiently refuse to buy it because of transaction costs. When instead property rights are weak, low-valuation potential buyers inefficiently expropriate the original owners' property. The trade-off between these two misallocations entails that property rights will be weaker the larger transaction costs are regardless of whether they are driven by frictions outside the control of traders or determined by the mix of the dispersion in their valuation and either the original owners' market power or their privileged information. A similar conclusion holds true for an upstream firm's property rights on an input necessary to a downstream firm to introduce a new technology and whose cost is random and ex ante non contractible. This time, transaction costs rise with the likelihood of a more productive technology. All these implications survive when a group of traders/innovators has a larger political influence on institutional design and when the disincentive to effort effect of weak property rights is taken into account. Crucially, the model predictions are consistent with the negative effects of proxies for market frictions and failures on measures of the protection of personal, intellectual, and financial property for a panel of 135 countries spanning the 2006-2015 period. Evidence from several identification strategies suggests that these relationships are indeed causal.
Keywords: D23; L11; P14; Z10; 330; Property Rights; Transaction Costs; Market Frictions; Market Failures